Concomitant use of benzodiazepine and alcohol in methadone‐maintained patients from the ANRS–Methaville trial: Preventing the risk of opioid overdose in patients who failed with buprenorphine. (30th September 2015) - Roux, Perrine; Lions, Caroline; Michel, Laurent; Vilotitch, Antoine; Mora, Marion; Maradan, Gwenaelle; Marcellin, Fabienne; Spire, Bruno; Alain, Morel; Patrizia, Carrieri M.; ,
Abstract: Introduction and Aims: Concomitant elevated alcohol consumption and use of benzodiazepines (BZD) during methadone treatment is widespread and particularly worrying because of the increased risk of overdose. Using concomitant binge drinking and use of BZD as a proxy of overdose risk, we aimed to study whether buprenorphine switchers were at higher risk of overdose during methadone treatment. Design and Methods: The French National Agency for Research for Aids and Viral Hepatitis –Methaville multisite randomised trial enrolled 195 patients to assess the feasibility of initiating methadone in primary care by comparing it with methadone initiation in specialised centres. We selected 174 patients with available data on BZD use and alcohol binge drinking at baseline and 12 months, accounting for 318 visits. The outcome was defined to take into account an overdose risk gradient as follows: no BZD use, BZD use without and with binge drinking during the previous month. To identify factors associated with the outcome, we performed a mixed multinomial logistic regression analysis. Results: At baseline, 26% of the sample reported BZD use alone while 16% reported BZD use and binge drinking. Half of the sample (51%) was switching from buprenorphine treatment. After multivariate analysis, employment, depressive symptoms and switching treatment from buprenorphine to methadone [odds ratio (95% confidence interval) 5.38 (1.74–16.62)] remained associated with BZD use and binge drinking. Discussion and Conclusions: As well as the importance of identifying socially vulnerable and depressed methadone‐maintained patients, clinicians should be aware that patients who fail buprenorphine treatment and switch to methadone require greater clinical monitoring and management to avoid the risk of overdose. [Roux P, Lions C, Michel L, Mora M, Maradan G, Marcellin F, Spire B, Alain M, Patrizia CM, the ANRS Methaville Study Group. Concomitant use of benzodiazepine and alcohol in methadone‐maintained patients from the ANRS Methaville trials: Preventing the risk of opioid overdose in patients who failed with buprenorphine. Drug Alcohol Rev 2015; ●●:●●–●●]